19. Mātiro Whakamua: Looking Over the Horizon - Bargh, Maria; MacArthur, Julie (Environmental politics and policy in Aotearoa New Zealand, 2022)
Keywords: environment; environmental conditions; environmental protection; government relations; social conditions; tiriti o waitangi/treaty of waitangi

18. Te Mana o te Wai: The Modern Politics of Freshwater - Ruru, Jacinta (Environmental politics and policy in Aotearoa New Zealand, 2022)
Keywords: environment; environmental conditions; environmental protection; government relations; social conditions; tiriti o waitangi/treaty of waitangi

15. Imperialism and Systems of Stuff - Ngata, Tina (Environmental politics and policy in Aotearoa New Zealand, 2022)
Keywords: environment; environmental conditions; environmental protection; government relations; social conditions; tiriti o waitangi/treaty of waitangi

14. Te Taiao and 'Biodiversity' - Bargh, Maria; Malcolm, Tame (Environmental politics and policy in Aotearoa New Zealand, 2022)
Keywords: environment; environmental conditions; environmental protection; government relations; social conditions; tiriti o waitangi/treaty of waitangi

11. How to Write a Press Release - Tapsell, Ellen (Environmental politics and policy in Aotearoa New Zealand, 2022)
Environmental Politics and Policy in Aotearoa New Zealand is a comprehensive introduction to confronting some of today's most urgent challenges. Global warming, threats to biodiversity, contamination of waterways and other environmental issues confront today's citizens with critical challenges that are fundamentally political. Power, authority and state action enable current practices - and through politics and policy that power can be harnessed to create a more ecologically sustainable planet. In this book, leading scholars from around Aotearoa introduce students to environmental politics and policy based in this country's unique institutional, cultural and resource context. The text focuses on the key importance of Te Tiriti o Waitangi, the characteristics of the natural environment in Aotearoa and the role of gender dynamics in the distribution of power, before turning to how this unique setting informs and is, in turn, informed by the global context of environmental politics. The authors take a systemic view of environmental politics and governance in New Zealand, addressing the philosophical and ideational debates about who and what matters (both human and non-human), the political institutions that embed and enact these ideas, and how these ideas then manifest in particular arenas - from climate and freshwater to energy and farming. Practical tips - how to make a submission, organise a protest, write a policy brief or a press release - are woven throughout.
Keywords: environment; environmental conditions; environmental protection; government relations; social conditions; tiriti o waitangi/treaty of waitangi

10. Social Movements and the Environment - Kurian, Priya; Cretney, Raven; Munshi, Debashish; Morrison, Sandra L. (Environmental politics and policy in Aotearoa New Zealand, 2022)
Environmental Politics and Policy in Aotearoa New Zealand is a comprehensive introduction to confronting some of today's most urgent challenges. Global warming, threats to biodiversity, contamination of waterways and other environmental issues confront today's citizens with critical challenges that are fundamentally political. Power, authority and state action enable current practices - and through politics and policy that power can be harnessed to create a more ecologically sustainable planet. In this book, leading scholars from around Aotearoa introduce students to environmental politics and policy based in this country's unique institutional, cultural and resource context. The text focuses on the key importance of Te Tiriti o Waitangi, the characteristics of the natural environment in Aotearoa and the role of gender dynamics in the distribution of power, before turning to how this unique setting informs and is, in turn, informed by the global context of environmental politics. The authors take a systemic view of environmental politics and governance in New Zealand, addressing the philosophical and ideational debates about who and what matters (both human and non-human), the political institutions that embed and enact these ideas, and how these ideas then manifest in particular arenas - from climate and freshwater to energy and farming. Practical tips - how to make a submission, organise a protest, write a policy brief or a press release - are woven throughout.
Keywords: environment; environmental conditions; environmental protection; government relations; social conditions; tiriti o waitangi/treaty of waitangi

3. Environmental Ideas in Aotearoa - Mutu, Margaret (Environmental politics and policy in Aotearoa New Zealand, 2022)
Environmental Politics and Policy in Aotearoa New Zealand is a comprehensive introduction to confronting some of today's most urgent challenges. Global warming, threats to biodiversity, contamination of waterways and other environmental issues confront today's citizens with critical challenges that are fundamentally political. Power, authority and state action enable current practices - and through politics and policy that power can be harnessed to create a more ecologically sustainable planet. In this book, leading scholars from around Aotearoa introduce students to environmental politics and policy based in this country's unique institutional, cultural and resource context. The text focuses on the key importance of Te Tiriti o Waitangi, the characteristics of the natural environment in Aotearoa and the role of gender dynamics in the distribution of power, before turning to how this unique setting informs and is, in turn, informed by the global context of environmental politics. The authors take a systemic view of environmental politics and governance in New Zealand, addressing the philosophical and ideational debates about who and what matters (both human and non-human), the political institutions that embed and enact these ideas, and how these ideas then manifest in particular arenas - from climate and freshwater to energy and farming. Practical tips - how to make a submission, organise a protest, write a policy brief or a press release - are woven throughout.
Keywords: environment; environmental conditions; environmental protection; government relations; social conditions; tiriti o waitangi/treaty of waitangi

Ngā Whai Take: Reframing Indigenous Development - Ruwhiu, Diane; Amoamo, Maria; Carter, Lynette; Bargh, Maria; Ruckstuhl, Katharina; Carr, Anna; Awatere, Shaun (The Routledge Handbook of Indigenous Development, 2022)
This chapter explores how Maori developmental aspirations require a multidimensional view of economy linked to Maori identity, landscape and worldview. It aims to reframe the Maori, and, by extension, wider concepts of Indigenous economy to one that has meaning to Maori communities, and thus more holistically appreciates the true notion of ‘value’. The chapter presents Maori business case studies that illustrate distinctive elements of connection between Maori worldview, forms of organization and economy. It offers insight into how we might realize meaningful development for Indigenous communities more broadly. Non-economic variables such as relationships, reciprocity and connection are privileged, and matauranga Maori, identity, tikanga Maori, whanaungatanga, whakapapa, and manaakitanga guide Maori business structure, governance and practice. Whai take represents a broader conceptualization of Maori economy that more meaningfully engages the multifaceted nature of Maori socio-economic activity.
Keywords: economic development; rangatiritanga; te ao Māori; whanaungatanga

Women, incarceration and settler colonial control - McIntosh, Tracey (Women, Crime and Justice in Context: Contemporary Perspectives in Feminist Criminology from Australia and New Zealand, 2022)
This chapter examines settler colonial crime control and its impacts on Indigenous women. High rates of victimisation and high levels of over-policing and over-incarceration mark Indigenous people’s experience of settler colonialism. This chapter explores the historical and contemporary conditions of colonialism through a gender lens, exploring in particular the impact of prison on Indigenous women’s lives. The chapter is based on an interview with and subsequent written notes by Professor McIntosh in 2020 discussing women, incarceration and settler colonial control in the Aotearoa New Zealand setting.
Keywords: criminalisation; crown policy; crown violence; incarceration; prison; racism; wāhine māori

Settler violence, family, and whānau violence in Aotearoa New Zealand - McIntosh, Tracey (Women, Crime and Justice in Context: Contemporary Perspectives in Feminist Criminology from Australia and New Zealand, 2022)
This chapter looks at the impact on M?ori that colonial and neo-colonial practices of dispossession and immiseration have had on elevated family violence rates in Aotearoa New Zealand. In reflecting on interpersonal violence, it seeks to locate systemic forms of violence, such as legislative violence, institutional violence, and economic violence, and their relationship with family violence. It draws on David Nixon’s (2011) notion of slow violence to look at the intergenerational harm of poverty, racism, and entrenched negative social issues. The focus then moves to Indigenous solutions to family violence that demonstrate the power of lived experience and social and cultural expertise to support healing and transformation in M?ori communities.
Keywords: crown policy; crown violence; dispossession; family violence; intergenerational trauma; land loss

Māori Perspectives on Conscious Capitalism - Dell, Kiri; Houkamau, Carla; Mika, Jason; Newth, Jamie (The Spirit of Conscious Capitalism: Contributions of World Religions and Spiritualities, 2022)
Māori, the Indigenous peoples of Aotearoa New Zealand, were formerly colonised by the British from 1840 following the signing of te Tiriti o Waitangi (the Treaty of Waitangi). Māori remain numerically significant in New Zealand and are the second largest ethnic group after Pākehā (New Zealand Europeans). Pre-colonial, traditional Māori society, through collective economic practice, was balanced to protect whakapapa (geological relationships) and natural resources. This balance was key to survival, and cultural practices evolved to maintain this balance. Despite the ongoing impacts of colonisation since the 1800s, Māori have maintained strong cultural values, which manifest in contemporary approaches to business that strive to balance the interests of future and past generations based on a spiritual connection to the natural world. Conscious capitalism, as envisioned by Mackey and Sisodia (2014), describes higher-order principles that align with Māori approaches to business, but their limitation is articulating the role of spirituality in entrepreneurial activity. This chapter extends Mackey and Sisodia’s higher-order tenets drawing on Māori values, primarily, mana (a supernatural force for status in a person, place, or object) and hau (the practice of reciprocal relations) to articulate how spiritual and cultural values shape contemporary Māori business endeavours. To illustrate, we offer a case study of a Māori business, led by one of the authors, which is grappling with tensions between cultural and commercial imperatives.
Keywords: capitalism; mana party; unsure if politics

Indigenous Peoples, Data, and the Coloniality of Surveillance - Cormack, Donna; Kukutai, Tahu (New Perspectives in Critical Data Studies: The Ambivalences of Data Power, 2022)
In Aotearoa New Zealand (Aotearoa NZ), Māori (the Indigenous peoples of New Zealand) have long been objects of surveillance by state institutions and agents. State representations have centred on constructions of difference and deviance, on understandings of Indigenous peoples as dangerous, and on the management of Indigenous resistance to colonialism. This chapter considers how contemporary state surveillance practices in Aotearoa NZ, enabled by the expanded use of big data and linked government datasets, function to regulate and manage Māori. Through this lens, we explore continuities of current data practices for Indigenous peoples with the racialised logics and social orders set in place as part of global systems of imperialism and colonialism. Recognising that resistance has always been a part of Indigenous responses to colonialism, we also explore how Māori Data Sovereignty (MDSov), as part of broader Indigenous Data Sovereignty (IDS) movements globally, provides opportunities to counter and disrupt prevailing data relations and to imagine alternative futures.
Keywords: colonisation; data; data sovereignty; indigenous data sovereignty; surveillance